2016
DOI: 10.1016/j.jobcr.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the impacted mandibular third molars on fractures of the mandibular angle and condyle – A prospective clinical study

Abstract: Practice of prophylactic removal of mandibular third molar and resultant strengthening of angle region should be reconsidered, as it increases the risk of fracture at condylar region which is difficult to treat and associated with more morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
2
9
2
4
Order By: Relevance
“…A similar result was established by Safdar and Meechan, Tiwari et al, and Halmos et al111719 The frequency of condyle fractures was found more in patients with absence of mandibular third molars or the ones who did not have impacted ones (79% erupted) as put forth by Zhu et al, Duan and Zhang, and Iida et al121620 However, study of Ugboko et al conflicted with most of the researches and depicted that third molars were not a predisposing factor for angle fractures 21. Thus, prophylactic extractions of symptom-free mandibular third molars may strengthen the angle region, but at the same time the force generated may fracture the mandible elsewhere, especially the condyle 17. A theory that the presence of a mandibular third molar tends to reduce the cross-section area of the angle which in turn reduces the tensile strength of the bone, encouraging the propagation of fracture along the path of least resistance, was supported by Safdar and Meechan and Ma'aita and Alwrikat,1122 but was in conflict with Wolujewicz, Tevepaugh and Dodson, and Lee and Dodson who failed to establish this relation 82324.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…A similar result was established by Safdar and Meechan, Tiwari et al, and Halmos et al111719 The frequency of condyle fractures was found more in patients with absence of mandibular third molars or the ones who did not have impacted ones (79% erupted) as put forth by Zhu et al, Duan and Zhang, and Iida et al121620 However, study of Ugboko et al conflicted with most of the researches and depicted that third molars were not a predisposing factor for angle fractures 21. Thus, prophylactic extractions of symptom-free mandibular third molars may strengthen the angle region, but at the same time the force generated may fracture the mandible elsewhere, especially the condyle 17. A theory that the presence of a mandibular third molar tends to reduce the cross-section area of the angle which in turn reduces the tensile strength of the bone, encouraging the propagation of fracture along the path of least resistance, was supported by Safdar and Meechan and Ma'aita and Alwrikat,1122 but was in conflict with Wolujewicz, Tevepaugh and Dodson, and Lee and Dodson who failed to establish this relation 82324.…”
Section: Discussionsupporting
confidence: 86%
“…Our group A (angle fractures) results were contradicted by findings of Mah et al, who found assault or being struck by an object to be a more relevant cause of fracture; however, their results complemented our group B (condyle fractures) etiology which was followed by road traffic accidents 1. Tiwari et al put forth that road traffic accidents were responsible for both angle and condyle fractures attributing up to 25% of patients with erupted mandibular third molars and 42% without third molars 17. Zhu et al depicted two groups—one with unerupted third molars in which assault was a major etiological factor (41.6%) and the other without third molars in which assaults occupied 37.6% of the factors 12…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Tako je u jednoj retrospektivnoj studiji iranskih autora ustanovljeno da impaktirani umnjak povećava rizik za prelom ugla, dok istovremeno umanjuje rizik od pojave preloma kondilarnog nastavka donje vilice. Prelomi ugla donje vilice češće se javljaju kod pacijenata kod kojih je impaktirani umnjak postavljen bliže površini kosti nego kod pacijenata sa duboko impaktiranim umnjacima (15,20,21,22).…”
Section: Diskusijaunclassified